Microstructural X-Ray Computed Tomography Investigation of the Defect Evolution in Refractory Castings Based on Andalusite - Anita Razavi; Vanessa Hopp; Dominik Hahn; Almuth Sax; Peter Quirmbach (Ceramics)
X-ray computed tomography (XRT) has gradually established its position as a non-destructive and, therefore, reproducible three-dimensional (3D) investigation technique, allowing for material- and geometry-independent applications. In the context of this study, XRT provides an enhanced understanding of thermal-induced microstructural changes in an andalusite-based refractory, which are not apparent from the limited two-dimensionality of conventional optical investigation techniques. By subjecting an andalusite-based sample to an XRT scan after temperature treatments of T = 110 °C, 800 °C, 1000 °C, 1200 °C and 1400 °C, the XRT technique in this study introduced a novel perspective on the sintering process of andalusite refractory materials. The XRT investigation focused on the thermal-induced defect and crack evolution of the castable as a function of temperature. In addition to general sintering phenomena, this includes the formation of a capillary network filled with silica-rich glass phases (SiO2) due to the mullitization of andalusite. The results of the XRT analysis indicate the existence of glass bridges within these structures.